Kif1c regulates osteoclastic bone resorption as a downstream molecule of p130Cas. (30th December 2019) - Kobayakawa, Miki; Matsubara, Takuma; Mizokami, Akiko; Hiura, Fumitaka; Takakura, Nana; Kokabu, Shoichiro; Matsuda, Miho; Yasuda, Hisataka; Nakamura, Ichiro; Takei, Yosuke; Honda, Hiroaki; Hosokawa, Ryuji; et al.
Abstract : Podosome formation in osteoclasts is an important initial step in osteoclastic bone resorption. Mice lacking c‐Src (c‐Src −/− ) exhibited osteopetrosis due to a lack of podosome formation in osteoclasts. We previously identified p130Cas (Crk‐associated substrate [Cas]) as one of c‐Src downstream molecule and osteoclast‐specific p130Cas‐deficient (p130Cas ΔOCL−/− ) mice also exhibited a similar phenotype to c‐Src −/− mice, indicating that the c‐Src/p130Cas plays an important role for bone resorption by osteoclasts. In this study, we performed a cDNA microarray and compared the gene profiles of osteoclasts from c‐Src −/− or p130Cas ΔOCL−/− mice with wild‐type (WT) osteoclasts to identify downstream molecules of c‐Src/p130Cas involved in bone resorption. Among several genes that were commonly downregulated in both c‐Src −/− and p130Cas ΔOCL−/− osteoclasts, we identified kinesin family protein 1c (Kif1c), which regulates the cytoskeletal organization. Reduced Kif1c expression was observed in both c‐Src −/− and p130Cas ΔOCL−/− osteoclasts compared with WT osteoclasts. Kif1c exhibited a broad tissue distribution, including osteoclasts. Knockdown of Kif1c expression using shRNAs in WT osteoclasts suppressed actin ring formation. Kif1c overexpression restored bone resorption subsequent to actin ring formation in p130Cas ΔOCL−/− osteoclasts but not c‐Src −/− osteoclasts, suggesting that Kif1c regulates osteoclastic bone resorption in the downstream of p130Cas (191 words). Significance of the study: We previously showed that the c‐Src/p130Cas (Cas) plays an important role for bone resorption by osteoclasts. In this study, we identified kinesin family protein 1c (Kif1c), which regulates the cytoskeletal organization, as a downstream molecule of c‐Src/p130Cas axis, using cDNA microarray. Knockdown of Kif1c expression using shRNAs in wild‐type osteoclasts suppressed actin ring formation. Kif1c overexpression restored bone resorption subsequent to actin ring formation in osteoclast‐specific p130Cas‐deficient (p130Cas ΔOCL−/− ) osteoclasts but not c‐Src −/− osteoclasts, suggesting that Kif1c regulates osteoclastic bone resorption in the downstream of p130Cas.